2006
DOI: 10.1111/j.1528-1167.2006.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

School Performance of Nigerian Adolescents with Epilepsy

Abstract: Summary: Purpose:The study assessed the school performance of Nigerian adolescents with epilepsy compared with healthy controls and examined the variables correlating with their academic difficulties.Methods: The school grades of adolescents with epilepsy aged 12 to 18 years (n = 73) over the past academic year were compared with the grades of their classmates of the same age and gender. Risk factors possibly associated with school performance, such as adolescent variables (age, gender, perceived stigma, attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…in a very different situation from these village children. Nigerian children, with treated epilepsy, attending primary school, demonstrate no gross differences from their peers 14 , whereas the poor academic performance of some Nigerian adolescents with epilepsy was attributed to familial psychosocial problems or their own adverse reaction to the diagnosis 15 . The possible impact of epilepsy on school attendance or performance needs to be considered in its local context, and compared with 'typical progress' in rural primary schools 16 .…”
Section: Discussionmentioning
confidence: 93%
“…in a very different situation from these village children. Nigerian children, with treated epilepsy, attending primary school, demonstrate no gross differences from their peers 14 , whereas the poor academic performance of some Nigerian adolescents with epilepsy was attributed to familial psychosocial problems or their own adverse reaction to the diagnosis 15 . The possible impact of epilepsy on school attendance or performance needs to be considered in its local context, and compared with 'typical progress' in rural primary schools 16 .…”
Section: Discussionmentioning
confidence: 93%
“…[14] Consequently, unemployment and underemployment are more common among PWE. [12] In addition, studies have shown that epilepsy affects the intellectual abilities of PWE, which may have a negative effect on the overall school performance, [16][17][18][19] and factors associated with poor intelligence include seizure type; [16] seizure frequency, long duration of epilepsy, early age of onset of seizure 17 ; and status epilepticus. [16] In china, epilepsy diminishes the prospect of marriage, especially for women, [20] and in China and India it is commonly viewed as a reason for prohibiting and annulling marriages.…”
Section: Introductionmentioning
confidence: 99%
“…Dutch study of epilepsy in childhood (DuSECh) (2003) revealed that despite similar intelligence and educational background 51% of children with idiopathic epilepsy required special educational assistance, compared with 27% of healthy control subjects 5 . Nigerian investigators observed that the mean school grades of adolescents with epilepsy is significantly lower than are those of their healthy controls 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Disease related factors such as early onset seizures, long duration of epilepsy 6 , partial onset seizures, partial seizures with secondary generalisation 11 , and adverse effects of medication 12 have been implicated by some authors. Psychosocial factors like stigma, the child feeling different to others, overprotection, lack of awareness by the parents and teachers 10 have been attributed by others.…”
Section: Discussionmentioning
confidence: 99%